Social Avoidance and Social Adjustment: The Moderating Role of Emotion Regulation and Emotion Lability/Negativity Among Chinese Preschool Children - Zhu, Jingjing; Xiao, Bowen; Hipson, Will; Yan, Chenyu; Coplan, Robert J.; Li, Yan (Frontiers in Psychology, 2021)
The present study explored the role of emotion regulation and emotion lability/negativity as a moderator in the relation between child social avoidance and social adjustment (i.e., interpersonal skills, asocial behavior, peer exclusion) in Chinese culture. Participants were N = 194 children (102 boys, 92 girls, Mage = 70.82 months, SD = 5.40) recruited from nine classrooms in two public kindergartens in Shanghai, People’s Republic of China. Multi-source assessments were employed with mothers rating children’s social avoidance and teachers rating children’s emotion regulation, emotion lability/negativity and social adjustment outcomes. The results indicated that the relations between social avoidance and social adjustment difficulties were more negative among children lower in emotion regulation, but not significant for children with higher emotion regulation. In contrast, the relations between social avoidance and social adjustment difficulties were more positive among children higher in emotion lability/negativity, but not significant for children with lower emotion lability/negativity. This study informs us about how emotion regulation and emotion lability/negativity are jointly associated with socially avoidant children’s development. As well, the findings highlight the importance of considering the meaning and implication of social avoidance in Chinese culture.